FACTORS DIFFERENTIATING HIGH AND LOW PAIN INTERFERENCE IN PERSONS WITH DEMENTIA. (11th November 2018) - Block, P; Amspoker, A; Snow, A; Renn, B; Pickens, S; Kunik, M
Abstract: Pain is highly prevalent in persons with dementia (PWDs), yet under detected and poorly treated. Pain interference, the degree to which pain interferes with a person's ability to function, is a key measure of pain treatment outcomes. However, there has been little examination of pain interference in PWDs. Our study sought to identify factors that differentiate PWDs experiencing high versus low pain interference. The sample consisted of 92 community-dwelling PWDs and their caregivers that were randomized to receive a home-based 8-week psychosocial intervention to reduce aggression in PWDs with pain (versus enhanced primary care). Pain interference was assessed at the beginning of the first intervention session. The interventionist obtained caregiver/proxy report as to whether the PWD's pain interfered with 6 activities (e.g., sleeping, daily chores). Pain interfering with 0 to 1 activities was classified as "low pain interference" (n=24) and pain interfering with 4 to 6 activities was classified as "high pain interference" (n=31); this selection resulted in a final sample of 55. Analyses compared the high and low pain interference groups (as defined by caregiver reports) on the following factors: PWD depression, caregiver burden, PWD-caregiver mutuality, and PWD demographics. Among the higher pain interference group, caregiver burden and PWD depression were significantly higher (t (53) = -2.14, p = .037 and t (52) = -3.41, p = .0013, respectively). Accurate assessment of pain in PWDs is challenging due to dementia's effects on self-report; these findings may highlight the importance of obtaining caregiver-reported pain interference ratings.